ANALISIS KAUSALITAS DANA DESA, PEMBANGUNAN INFRASTRUKTUR, DAN KESEJAHTERAAN MASYARAKAT DI KECAMATAN GONDANGREJO KABUPATEN KARANGANYAR - Egidea Amengku Sukma; Inda Fresti Puspitasari (STKIP Persada Khatulistiwa Sintang, 2023)
All villages in Gondangrejo District are classified as self-sufficient villages, have a well-known agricultural sector, have high-quality industrial areas, are quite large, and function as economic developers. However, because the carrying capacity of infrastructure is very low due to the absorption capacity used for handling Covid-19, many roads have been damaged and connections between villages have not been tendered. This study aims to observe the pattern of causality between infrastructure, village funds and the level of community welfare in Gondangrejo District, Karanganyar Regency in 2017-2021. This study uses the Granger Causality Test method. In the Granger Causality test, the data requirements used are stationary data. The results of the Granger Causality Test state that there is a one-way causality relationship between the level of welfare affecting village funds and a two-way causality between village funds causing or influencing infrastructure and vice versa. Based on these results, it is hoped that the village government can pay more attention and study more in the management of village funds. Further review needs to be carried out in carrying out the infrastructure development needed by the community, so that the absorbed village funds will produce infrastructure that is directly useful for the economic activities of the villagers.